UPAYA MENINGKATKAN HASIL BELAJAR EKONOMI MELALUI STRATEGI PEMBELAJARAN GROUP RESUME - Husna, Isnaini; Hidayat, Nurdin (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2020)
The problems in this study are: (1) the economic learning outcomes of class XI students. IPS 4 is still low, (2) the lack of variety of learning strategies used. The purpose of this study was to improve the activities and economic learning outcomes of class XI students. IPS 4 used a group resume learning strategy in economic subjects in SMA Negeri 14 Bandar Lampung in the academic year 2019/2020. The method used is Classroom Action Research (CAR) which is carried out in two stages of a cycle which in its application uses a group resume learning strategy. The subjects in this study were students of class XI.IPS 4 SMA Negeri 14 Bandar Lampung, amounting to 34 students. Data collection techniques were carried out through tests using 40 question sheets and observation sheets. The data analysis technique was carried out to analyze the activity data and student learning outcomes. The results showed the percentage of student learning activities increased from 58.72% in the first cycle to 78.50% in the second cycle. The percentage of student learning outcomes also increased from 67.65% in the first cycle and 85.29% in the second cycle. So it can be concluded that learning activities by applying a group resume learning strategy can improve economic learning activities and outcomes of students in class XI.IPS 4 SMA Negeri 14 Bandar Lampung in the academic year 2019/2020